Self-assembled mononuclear complexes: open metal sites and inverse dimension-dependent catalytic activity for the Knoevenagel condensation and CO2 cycloaddition. Issue 42 (21st October 2022) - Xu, Heng; Zhang, Le-Xi; Xing, Yue; Yin, Yan-Yan; Tang, Bo; Bie, Li-Jian
Abstract : Molecular complexes based on Cu or Zn were selected as heterogeneous catalysts for efficient and stable Knoevenagel condensation and CO2 cycloaddition. DFT demonstrated that the change in coordination mode accelerates the reactions. Abstract : To lessen the greenhouse effect, measures such as improving the recovery of crude oil and converting carbon dioxide (CO2 ) into valuable chemicals are necessary to create a sustainable low-carbon future. To this end, the development of efficient new oil-displacing agents and CO2 conversion has aroused great interest in both academia and industry. The Knoevenagel condensation and CO2 cycloaddition are the key reactions to solve the above problems. Four Cu- or Zn-based molecular complexes built from different ligands possessing hydrophilic–hydrophobic layers and different dimensionalities were chosen as solid catalysts for this study. Structural analysis revealed the presence of hydrophilic–hydrophobic layers and open metal sites in the low-dimensional complexes. To obtain deep insight into the reaction mechanism, first-principles density functional theory (DFT) calculations were carried out. These calculations confirmed that in the Knoevenagel condensation reaction, the final formation of benzylidenemalononitrile is the rate-determining step (an energy barrier (Δ E ) value of 73.2 kJ mol −1 ). The zero-dimensional (0D) Cu molecular complex with unsaturated metal centers, hydrophilic and hydrophobic layers, exhibited higher catalytic activity (yield: 100%, temperature: room temperature, and time: 2 h) compared with one- and two-dimensional Cu complexes. In the presence of a 0D Zn complex co-catalyzed with Br − in the CO2 cycloaddition reaction, the Δ E value reduces to 35.5 kJ mol −1 for the ring opening of styrene oxide (SO), which is significantly lower than Br − catalyzed (80.9 kJ mol −1 ) reactions. The roles of unsaturated metal centers, hydrophilic–hydrophobic layers and dimensionality in the Knoevenagel condensation and CO2 cycloaddition were explained in the results of structure–activity relationships.